Diseño sismo resistente del edificio de oficinas con sistema mixto (acero y hormigón) - Cabrera Minga, Roberto Xavier (2016)
The main objective of this project is to understand the behavior of earthquake resistant mixed steel and concrete structures through structural design, understand the system and its application in individual cases the local environment. The earthquake and the risk that this might cause could be interpreted as the extent of losses, economic, social, environmental. At present seismic engineering it has facilities suitable for both new construction and rehabilitation of existing structures that do not meet safety standards, is neither sufficient nor satisfactory structural design that meets the requirements only present solutions codes and standards but also it requires a deep understanding of the behavior of structures to seismic loads The advantages of composite construction using concrete and steel as a whole, including the ability to cover large spans, low weight /resistance, speed of construction and resistance (made by steel), the economy, damping and stiffness (provided by the concrete), they have made today that this type of construction is gaining ground. By combining the best features of each material results as a product more economic and efficient structures. The slabs may be reinforced concrete or metal plates (steel deck), the construction of such slabs is done by placing metal plates and a concrete slab on them. The system has stud connectors, temperature and mesh steel rods that allow a slab composed of steel and concrete.